Slow dynamics of water confined in Newton black films1. Issue 29 (7th August 2015) - Chen, Meng; Lu, Xiancai; Liu, Xiandong; Hou, Qingfeng; Zhu, Youyi; Zhou, Huiqun
<x xml:space="preserve">Abstract</x> Macroscopic polarization effect and retardation of ions and ionic groups concertedly lead to slowdown of water dynamics in Newton black films.